A genome-wide analysis of MADS-box genes in peach [Prunus persica (L.) Batsch] - Wells, Christina E (BMC Plant Biol, 2015)
BACKGROUND: MADS-box genes encode a family of eukaryotic transcription factors distinguished by the presence of a highly-conserved ~58 amino acid DNA-binding and dimerization domain (the MADS-box). The central role played by MADS-box genes in peach endodormancy regulation led us to examine this large gene family in more detail. We identified the locations and sequences of 79 MADS-box genes in peach, separated them into established subfamilies, and broadly surveyed their tissue-specific and dormancy-induced expression patterns using next-generation sequencing. We then focused on the dormancy-related SVP/AGL24 and FLC subfamilies, comparing their numbers and phylogenetic relationships with those of other sequenced woody perennial genomes. RESULTS: We identified 79 MADS-box genes distributed across all eight peach chromosomes and frequently located in clusters of two or more genes. They encode proteins with a mean length of 248 ± 72 amino acids and include representatives from most of the thirteen Type II (MIKC) subfamilies, as well as members of the Type I Mα, Mβ, and Mγ subfamilies. Most Type I genes were present in species-specific monophyletic lineages, and their expression in the peach sporophyte was low or absent. Most Type II genes had Arabidopsis orthologs and were expressed at much higher levels throughout vegetative and fruit tissues. During short-day-induced growth cessation, seven Type II genes from the SVP/AGL24, AGL17, and SEP subfamilies showed significant changes in expression. Phylogenetic analyses indicated that multiple, independent expansions have taken place within the SVP/AGL24 and FLC lineages in woody perennial species. CONCLUSIONS: Most Type I genes appear to have arisen through tandem duplications after the divergence of the Arabidopsis and peach lineages, whereas Type II genes appear to have increased following whole genome duplication events. An exception to the latter rule occurs in the FLC and SVP/AGL24 Type II subfamilies, in which species-specific tandem duplicates have been retained in a number of perennial species. These subfamilies comprise part of a genetic toolkit that regulates endodormancy transitions, but phylogenetic and expression data suggest that individual orthologs may not function identically across all species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-015-0436-2) contains supplementary material, which is available to authorized users.